Gender specifics of the association between blood fibrinolytic activity and cardiovascular disease or diabetes mellitus in a cohort of Muscovites aged 55 years or older - L. A. Ratnikova; V. A. Metelskaya; N. V. Perova; A. D. Deev; S. A. Shalnova (Кардиоваскулярная терапия и профилактика)
Aim. To investigate potential gender differences in the association between plasma fibrinolytic activity (FLA) and atherosclerotic pathology in elderly people. Material and methods. This analysis was performed as a part of the prospective population-based cohort study “Stress, Ageing, and Health in Russia”. The study included randomly selected Moscow residents of both genders and age of ≥55 years (n=1863; 889 men and 974 women). Based on the levels of blood FLA (time of spontaneous lysis of euglobin blood fraction, or euglobin lysis time, ELT), all participants were divided into three groups: with normofibrinolysis (ELT 180-260 minutes), hypofibrinolysis (ELT >260 minutes), and hyperfibrinolysis (ELT <180 minutes). Results. In this cohort of elderly Muscovites, the association between FLA and the presence of cardiovascular disease (CVD) or Type 2 diabetes mellitus (DM-2) differed in men and women. The link between hypofibrinolysis, atherogenic changes in lipid profile, or high fasting levels of insulin and arterial hypertension (AH), myocardial infarction (MI), or DM-2 was present only in men. In women, either reduced or increased FLA was not related to DM-2. Men with hyperfibrinolysis demonstrated lower odds of AH and DM-2, while women with hyperfibrinolysis had lower odds of AH, coronary heart disease, or angina. Conclusion. In elderly people, high FLA appears to provide protection against atherothrombotic pathology, regardless of gender. Low FLA was associated with higher odds of CVD and DM-2 in men only.